Inflammatory microRNAs in gastric mucosa are modulated by Helicobacter pylori infection and proton-pump inhibitors but not by aspirin or NSAIDs. - Riccardo Vasapolli; Marino Venerito; Wiebke Schirrmeister; Cosima Thon; Jochen Weigt; Thomas Wex; Peter Malfertheiner; Alexander Link (PLoS ONE, 2021)
Gastric carcinogenesis is associated with alterations of microRNAs (miRNAs) and reversal of these alterations may be a crucial element in cancer prevention. Here we evaluate the influence of H. pylori eradication, low-dose aspirin (LDA), non-steroidal anti-inflammatory drugs (NSAIDs) and proton-pump inhibitors (PPI) on modification of inflammatory mucosal miRNAs miR-155 and miR-223 in Helicobacter pylori-infected and non-infected subjects. The study was performed in two parts: 1) interventional study in 20 healthy subjects with and without H. pylori infection or following eradication (each n = 10) where LDA (100 mg) was given daily for 7 days; 2) prospective case-control observational study (n = 188). MiR-155 and miR-223 expression was strongly linked to H. pylori-infection and in short-term view showed a trend for reversal after eradication. Daily LDA as well as regular NSAIDs showed no influence on miRNAs expression both in healthy subjects and patients, while regular PPI intake was associated with lower miR-155 expression in antrum of patients with chronic gastritis independent of density of neutrophils and mononuclear infiltrate. In summary, PPI but not LDA or NSAIDs were associated with modification of inflammatory miRNAs miR-155 and miR-223 in an H. pylori dependent manner. The functional role of inflammatory miR-155 and miR-223 in understanding of H. pylori-related diseases needs further evaluation.